2017
DOI: 10.24319/jtpk.7.145-152
|View full text |Cite
|
Sign up to set email alerts
|

Penataan Sertifikasi Kompetensi Awak Kapal Penangkap Ikan Di Indonesia

Abstract: Competence crew of fishing vessels is one of the main factors supporting the success of fishing operations. Mastery of crew competence evidenced by a certificate of competence gained through education and training as well as certification testing crew of the fishing vessel by the competent authority. Crew competency standards fishing vessels must conform to the size of the vessel (ship's length and gross tonnage) and area fishing operations. This study aims to assess the gap that occurs between the crew compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
0
0
5
Order By: Relevance
“…Most fishermen have competence as fishermen based on knowledge and skills acquired from generation to generation . This condition is supported by the results of Budiman's research [13] which shows that many Indonesian fishing vessel crews currently do not have a certificate of Indonesian maritime competence according to conventions that have been known in several countries, namely the Certificate of Expert in Nautical Fishing Vessels (ANKAPIN) Level I, II and III (Certificate of Competency for Deck Officer of Fishing Vessel Level I, II, III) for the deck section and Certificate of Technical Expert for Fishing Vessels (ATKAPIN) Level I, II and III for engine parts (Certificate of Competency for Engine Officer of Fishing Vessel) . The results showed that there was a gap in the competency certification of fishing vessel crews in the Palabuhanratu Nusantara Fisheries Port and the Nizam Zachman Ocean Fisheries Port, Jakarta.…”
Section: Condition Of the Previous Fishing Vessel Crewsupporting
confidence: 68%
“…Most fishermen have competence as fishermen based on knowledge and skills acquired from generation to generation . This condition is supported by the results of Budiman's research [13] which shows that many Indonesian fishing vessel crews currently do not have a certificate of Indonesian maritime competence according to conventions that have been known in several countries, namely the Certificate of Expert in Nautical Fishing Vessels (ANKAPIN) Level I, II and III (Certificate of Competency for Deck Officer of Fishing Vessel Level I, II, III) for the deck section and Certificate of Technical Expert for Fishing Vessels (ATKAPIN) Level I, II and III for engine parts (Certificate of Competency for Engine Officer of Fishing Vessel) . The results showed that there was a gap in the competency certification of fishing vessel crews in the Palabuhanratu Nusantara Fisheries Port and the Nizam Zachman Ocean Fisheries Port, Jakarta.…”
Section: Condition Of the Previous Fishing Vessel Crewsupporting
confidence: 68%
“…Sesuai dеngаn Peraturan Pemerintah (PP) Nomor 7 Tahun 2000 tentang Kepelautan untuk pengawakan kapal penangkap ikan bаhwа ѕеtіар kapal penangkap ikan уаng аkаn berlayar harus diawaki seorang Nakhoda kapal yang berperan sebagai awak kapal yang mempunyai kewenangan komando di atas sebuah kapal dan memiliki tanggung jawab atas keselamatan kapal dan awak kapal (Undang-Undang tahun 2008 tentang Pelayaran, 2008). Selain itu seorang Nakhoda dan bеbеrара perwira kapal harus memiliki sertifikat keahlian pelaut kapal penangkap ikan sesuai dеngаn daerah pelayaran, ukuran kapal dan sertifikat ketrampilan dasar pelaut (Budiman et al, 2016). Ini disebabkan oleh semakin besar ukuran kapal dan beroperasi di laut lepas maka kesulitan semakin tinggi sehingga minimal pengetahuan dan keahlian yang dimiliki harus sesuai.…”
Section: Pendahuluanunclassified
“…Pelaut yang memiliki tingkat sertifikasi ANKAPIN-I dikukuhkan menjadi mualim 1 untuk pelaut yang beroperasi atau bekerja di atas kapal yang panjangnya ≥ 24 meter dan berukuran >88 GT dapat melakukan pelayaran di semua perairan. Pelaut yang memiliki sertifikat tingkat ANKAPIN-I dapat melakukan pelayaran di semua daerah penangkapan ikan (Budiman et al 2016). Pemegang sertifikat ANKAPIN-II di kukuhkan menjadi Mualim I di kapal ikan ukuran 60-88 GT dengan panjang kapal 12 meter dan kurang dari 24 meter yang beroperasi pada perairan Indonesia tapi tidak termasuk ZEEI (Zona Ekonomi Eksklusif Indonesia).…”
Section: Pendahuluanunclassified